The impact of pediatric congenital heart disease on primary teeth structure: a histological study: Congenital heart disease effect on Teeth. - Raad, Huda; Shihab, Omed (Acta Biomedica Atenei Parmensis, 2023)
Congenital heart disease (CHD) is an abnormality in the structure or function of the cardio-circulatory system present at birth and the ventricular septal defect (VSD) is the most common CHD in children. This study aimed to determine any differences in the histological structure of primary teeth between both healthy children and those children with ventricular septal defects in Erbil City.Methods enrolled children were divided into two groups. Group I (control) & group II (CHD) aged between 6-10 years old. A total of 44 children were collected, (22 children) in each group. Enamel, dentin, and odontoblast layers were examined histologically. Unpaired t-test used for statistical analysis.Results: The histopathological sections showed a significant difference in enamel, dentin, and odontoblast layer thickness (255.8 ± 41.68- 406.4 ±46.39), (1156 ± 116.0 - 1320 ± 117.4) and (29.74 ± 7.66 -41.38 ± 12.06) respectively, with p values (P < 0.0001) for enamel and dentin layer, and P < 0.0004  for odontoblast layer. A study of the images in the CHD group showed that the tooth tissue lost its integrity and cohesion in some places, and the thickness of the enamel and dentin layer in this group was significantly reduced compared to group I.  Tissue loss in enamel, pulp, and dentin cell were observed. Also, connective tissue layers in the pulp were disrupted. Conclusions: CHD can alter the natural structure formation of primary teeth. Histologically, enamel, dentin, and odontoblasts layer thickness reduction are found in primary teeth in children with ventricular septal defects.